Pengembangan Aplikasi Geotagging Pemetaan Sungai Dengan Pendekatan Gamification - Abu Hasan Baskara; Herman Tolle; Agi Putra Kharisma (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Mostly Indonesian river has bad quality of water because of contamination, bad placement and there is a little habitat of the animal near it. Then those problems are the same with one of the rivers in Japan called Iwamoto. However those problems already solved because of the role of technology called â€œClear Water Projectâ€ Application. The application can be used to give information to user about the river's condition from the geotagging process and help to grow awareness about the bad condition of the river. So that the user will do the preservation of the river. Indonesia has the same problem so it can use the same solution to solve the problem by developing application called â€œGeotagging Pemetaan Sungaiâ€. The development of application will be customized with the condition in Indonesia. Information about the river's condition to be accurate, it will use Global Positioning System and Camera sensor. Gamification feature makes user always want to use the application, it needs to approach using the gamification concept. The result of usability testing is the application is passed the test of usability within the aspect of usefulness, ease of use, ease of learning and satisfaction that reach 85,906%, so can be concluded that the application called â€œGeotagging Pemetaan Sungaiâ€ is relatively easier to use by the user for giving information about the river's condition by using gamification's approach.